Concomitant Morphological Modifications of the Avian Eggshell, Eggshell Membranes and the Chorioallantoic Membrane During Embryonic Development - Halgrain, Maeva; Georgeault, Sonia; Bernardet, Nelly; Hincke, Maxwell T.; Réhault-Godbert, Sophie (Frontiers in Physiology, 2022)
The chicken eggshell (ES) consists of 95% calcium carbonate and 3.5% organic matter, and represents the first physical barrier to protect the developing embryo, while preventing water loss. During the second half of development, calcium ions from the inner ES are progressively solubilized to support mineralization of the embryonic skeleton. This process is mediated by the chorioallantoic membrane (CAM), which is an extraembryonic structure that adheres to the eggshell membranes (ESM) lining the inner ES. The CAM surrounds the embryo and all egg contents by day 11 of incubation (Embryonic Incubation Day 11, EID11) and is fully differentiated and functionally active by day 15 of incubation (Embryonic Incubation Day 15, EID15). In this study, we explored the simultaneous morphological modifications in the ES, ESM and the CAM at EID11 and EID15 by scanning electron microscopy. We observed that the tips of the mammillary knobs of the ES remain tightly attached to the ESM fibers, while their bases become progressively eroded and then detached from the bulk ES. Concomitantly, the CAM undergoes major structural changes that include the progressive differentiation of villous cells whose villi extend to reach the ESM and the ES. These structural data are discussed with respect to the importance of ES decalcification in providing the calcium necessary for mineralization of embryo’s skeleton. In parallel, eggshell decalcification and weakening during incubation is likely to impair the ability of the ES to protect the embryo. It is assumed that the CAM could counteract this apparent weakening as an additional layer of physical, cellular and molecular barriers against environmental pressures, including pathogens, dehydration and shocks. However, such hypothesis needs to be further investigated.